(untitled) (Chimica nella Scuola, 2022)
In physical chemistry courses, the teaching of the expansion work is often conducted with reference to the external pressure. This practice, consistent with the equations of the dynamics of the material point only in special cases and for finite transformations, can be avoided without mathematical burden and by highlighting the difference between system-based work and surroundings-based work, which has an important conceptual and practical role.